Analysis of the Impact of Supply Chain of Government Procurement, Investments and Human Development Index on the Level of Indonesian Community Welfare - Rotinsulu, Debby Christina; Kumaat, Robby Joan; Sumual, Jacline I. (International Journal of Supply Chain Management, 2021)
The role of the government in the welfare of the community with existing policies is expected to be able to alleviate existing poverty and form a better society in thinking and managing existing resources. The development of a region must also be supported by various budgets that will later support any planning activities that will be made by the government with the implementation of regional autonomy and fiscal decentralization policies. The consideration is that the regions know more about the needs and service standards for the people in their regions so that the provision of regional autonomy is expected to spur an increase in the welfare of the people in the regions through increased economic growth. The existence of an increase in decentralization funds transferred by the central government every year is expected to encourage an increase in the rate of economic growth. The rate of regional economic growth is positively and significantly influenced by human development. In essence, development is human development, so it is necessary to prioritize the allocation of procurements for this purpose in budget preparation. Human development is an indicator for the progress of a country. A country is said to be developed by looking at gross domestic income. This study aims to analyze the impact of supply chain of government procurement, investment, and the human development index on the level of welfare of the Indonesian people using multiple linear regression analysis. The results show that the government procurement and investment had a positive and significant effect on people's welfare while the human development index is not statistically significant.